When fortune smiles onthe poor: a storyof upward intragenerational social mobilityamong Malay Felda settlers - Mohd Fakhruddin, Faizah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper discusses the pattern of social mobility experienced by the first generation Malay FELDA settlers in a FELDA settlement located in Perak. Social mobility patterns are solely gauged by settlers’ socio-economic conditions that are compared between the settlers’ pre-migration and post migration period to the FELDA settlement. The study involved fieldwork conducted for a period of nine months from December 2014 to August 2015. The study used qualitative method using in-depth interviews and participant observation with thirty settlers. The results of the study show that all of the first generation experienced upward intragenerational social mobility due to their migration to the FELDA settlement. Factors such as better employment opportunities, stable earnings and property ownership offered by FELDA are regarded as important reasons for the settlers’ upward social mobility.